Preparation of cookies from banana flour, soy flour, and Moringa leaf flour as an emergency food product. Issue 1 (April 2020) - Hasan, N W; Putri, T P; Zainal,
Abstract: Emergency food is a processed food product specifically designed for consumption in post-natural disaster conditions. The food can be provided for 15 days until having adequate assistance. Emergency food products must meet the daily energy requirements of individuals, around 2100 kcal per day. One of the emergency food products is cookies. The purpose of this study was to evaluate the nutritional compound, hardness, and organoleptic properties of emergency food in the form of cookies, prepared from Saba banana flour, soy flour, and Moringa flour. The treatment in this research using a single factor, namely different composition of the flour with three variables and three replications. The three variables were F1 (banana flour 25%, soy flour 10%, and Moringa flour 10%), F2 (banana flour 15%, soy flour 15%, and Moringa flour 15%), and F3 (banana flour 20%, soy flour 20%, and Moringa flour 5%). The parameters were macro nutritional components, such as protein (Kjedhal extraction), fat content (Soxhlet method), and carbohydrate (difference method). It was also evaluated water content (wet basis by drying oven), ash content (furnace), fiber content, hardness (Texture analyzer), calorie (by calculation), and hedonic sensory test in terms of color, taste, aroma, and texture. The results showed that all treatments fulfill the calorie requirement of emergency food. In terms of hardness, F2 resulted in the hardest texture of cookies but still eatable. Organoleptic test results showed that cookies with the use of 20% banana flour, 20% soybean flour, and 5% moringa flour favored by the panelists.